Lead production waste storage warehouse impact on the atmosphere (Eurasian Journal of Ecology, 2023)
This article developed an environmental map with a diagram of the dispersion of harmful substances rising into the atmosphere, considering the impact of lead production waste storage waste on the environment and influence of wind directions also wind speeds on the spread of harmful substances rising into the atmospheric air. On this map, in order to determine the distance of dispersion of harmful substances from sources of pollution to the maximum permissible concentrations in the atmospheric air, it was evaluated to analyze the effects of local Hydrometeorological features and terrain on the distance of dispersion and the extent to which the concentrations of harmful substances of the same name released into the atmospheric air from neighboring production sites which can increase in the concentrations of harmful substances in question. The magnitude of the radius of distribution of harmful substances covering the area depicted by the diagram of dispersion from sources of pollution in the air of the atmosphere was determined depending on the parameters of sources of pollution, hydrometeorological conditions and features of the terrain. During the research work, the obtained data after collecting lichens on tree trunks and counting them with the help of transparent frames were collected in the form of a table and the quality of the air in the area where the source of pollution is located was determined. Lichenoindicational assessment of air pollution with slag dust rising into the atmosphere on windy days from the surface of the slag storage warehouse of the lead plant in Shymkent was evaluated by comparing special classification data and lichen coatings on the trees of the uncontaminated area.Key words: atmospheric air, sources of pollution, waste storage, wind speed, maximum concentration, ore dressing waste, seepage distance, concentrations of harmful substances, slag waste, maximum concentration of harmful substances, lead production waste storage waste, lichenoindication method.